2010
DOI: 10.1111/j.1478-3231.2010.02327.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic pyogenic liver abscess as a sign of colorectal cancer: a population-based 5-year follow-up study

Abstract: We conclude that cryptogenic PLA is an alarm that may signal colorectal cancer, especially among female patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…In a colitis-associated CRC mouse model, the proliferation of a genotoxic E. coli commensal strain, NC101, was demonstrated to be favored by an inflammatory milieu and thus promoted tumorigenesis of CRC [26]. Several clinical studies have demonstrated the relationship between CRC, PLA and K. pneumoniae in Taiwan [17], [18], [20]. The hazard ratio of CRC was 3.36 times greater for patients with PLA as reported in a nationwide population-based 5-year follow-up study comprised of 274 PLA patients and 1,370 randomly selected subjects [18].…”
Section: Resultsmentioning
confidence: 99%
“…In a colitis-associated CRC mouse model, the proliferation of a genotoxic E. coli commensal strain, NC101, was demonstrated to be favored by an inflammatory milieu and thus promoted tumorigenesis of CRC [26]. Several clinical studies have demonstrated the relationship between CRC, PLA and K. pneumoniae in Taiwan [17], [18], [20]. The hazard ratio of CRC was 3.36 times greater for patients with PLA as reported in a nationwide population-based 5-year follow-up study comprised of 274 PLA patients and 1,370 randomly selected subjects [18].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, patients with suspected CLA have shown to have higher risks of developing colorectal cancer on long-term follow-up. In a study by Lai et al 7 on patients with CLA; there is a 3.36 times greater risk of developing colorectal cancer in a 5 year follow-up, as compared with those who did not have CLA. A similar study by Mohsen et al 4 also showed the same increased risk of colorectal cancer in CLA.…”
Section: Discussionmentioning
confidence: 97%
“…These findings strongly suggest the role of colonic abnormalities as a probable cause of CLA. Several studies have now shown colonoscopy as a vital tool in both the diagnosis, as well as cancer surveillance in patients with CLA 4 5 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness of the clinical presentation and prognostic factors of high-risk patient groups is very important. Some studies have attempted to explore the clinical course and prognostic factors of PLA patients with underlying malignancy 12,16,18 ; however, an appropriate assessment of the risk factors for mortality regarding abscess characteristics and/or microbiological information was lacking in the previous reports. To identify prognostic factors for PLA patients with underlying malignancy, we conducted a retrospective study to collect detailed clinical information of these patients, including clinical manifestations, imaging and laboratory findings, microbiologic studies, treatment, and outcomes.…”
Section: Introductionmentioning
confidence: 97%